Analisis Perbedaan Preferensi Karir Mahasiswa Akuntansi (Studi Empiris pada Mahasiswa S1 Akuntansi di Kota Padang) - Mirza, Aisyah Riani; Fitria Sari, Vita (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study is aimed to determine whether there are differences in accounting students' career preferences before and after being given information about the pros and cons of public accountants and private accountants. This study utilizes Expectancy theory and Herzberg's two factor theory. The study's population consists of undergraduate accounting students in Padang City, and data is collected by a survey distributed directly and via google form to accounting students at six universities in Padang. Hypothesis testing employs non-parametric analysis, namely the McNemar test. The findings of the study indicated a notable distinction in the career choices of accounting students prior to and following the provision of pros and cons information, with a significant value of 0.001. Salary and work-life balance are two aspects that influence students' motivation and expectations while considering a career as a public or private accountant.